PENGARUH PROFITABILITAS, KEBIJAKAN DIVIDEN, PERTUMBUHAN PENJUALAN, ARUS KAS OPERASI, DAN VOLUME PERDAGANGAN SAHAM TERHADAP RETURN SAHAM(Studi Kasus pada Perusahaan Sektor Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia periode 2014-2017 - Muslih, Muhamad; Fitriah, Fitriah (EDUTECH CONSULTANT, 2019)
This study aims to analyze the factors that can affect stock returns. In this study, the variables of profitability, dividend policy, sales growth, operating cash flow, and volume of stock trading were used. This study intends to determine the effect of profitability, dividend policy, sales growth, operating cash flow, and stock trading volume on stock returns simultaneously and partially. This research is a study using quantitative research methods with the purpose of descriptive-causative nature. The unit of analysis that is the focus of this study is the consumer goods industry sector companies listed on the Indonesia Stock Exchange for the period 2014-2017 with a purposive sampling technique. This study used 12 research samples for three years of research and used panel data regression analysis with EViews 9. The results showed that profitability, dividend policy, sales growth, operating cash flow, and stock trading volume had an effect on simultaneous stock returns. Partially, the variable sales growth affects stock returns, while profitability, dividend policy, operating cash flow, and stock trading volume do not affect stock returns.